ANALISIS FAKTOR KEPUASAN DAN PRODUKTIVITAS KERJA PADA PEKERJA REHABILITASI SOSIAL PENYANDANG DISABILITAS INTELEKTUAL - Ananda Fansari Istiqomah; Ekawati Ekawati; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Social rehabilitation of persons with intellectual disabilities is an effort to restore and develop the abilities of individuals with disabilities in intellectual functions. carried out by social workers assisted by assistants and other professions who can support the rehabilitation process. In implementing services, social rehabilitation workers have a large workload both physically and mentally and require special expertise in their implementation. . The purpose of this study was to analyze factors related to job satisfaction and productivity of social rehabilitation workers with intellectual disabilities. The research design used was an observational analytic method with a cross sectional approach. The population in this study were 107 workers at BBRSPDI Kartini in Temanggung. The sample in this study amounted to 40 people using a purposive sampling method, namely workers who are directly related to the social rehabilitation process of persons with intellectual disabilities at BBRSPDI Kartini in Temanggung. The instruments used were questionnaires and observation sheets. Based on the results of the rank sparment statistical test, it shows that there is a correlation between work motivation (ρ-value = 0.008), supervision (ρ-value = 0.002), co-workers (ρ-value = 0,000), working environment conditions (ρ-value = 0,000) and salary (ρ-value = 0.001) with job satisfaction. The work productivity variable shows that there is a correlation between work motivation (ρ-value = 0.044), supervision (ρ-value = 0.008), and salary (ρ-value = 0.020) with work productivity, but there is no correlation between coworkers (ρ- value = 0.207) and working environment conditions (ρ-value = 0.237) on work productivity